Hybrid sterility genes in mice (Mus musculus): a peculiar case of PRDM9 incompatibility. Issue 12 (December 2021) - Forejt, Jiri; Jansa, Petr; Parvanov, Emil
Abstract : Hybrid sterility is a critical step in the evolution of reproductive barriers between diverging taxa during the process of speciation. Recent studies of young subspecies of the house mouse revealed a multigenic nature and frequent polymorphism of hybrid sterility genes as well as the recurrent engagement of the meiosis-specific gene PR domain-containing 9 ( Prdm9 ) and X-linked loci. Prdm9 -controlled hybrid sterility is essentially chromosomal in nature, conditioned by the sequence divergence between subspecies. Depending on the Prdm9 interallelic interactions and the X-linked Hstx2 locus, the same homologs either regularly recombine and synapse, or show impaired DNA DSB repair, asynapsis, and early meiotic arrest. Thus, Prdm9 -dependent hybrid sterility points to incompatibilities affecting meiotic recombination as a possible mechanism of reproductive isolation between (sub)species. Highlights: House mouse subspecies provide excellent models of early stages of speciation. They show incomplete reproductive isolation with the formation of hybrid zones and polymorphic hybrid sterility genes. Genetic control of hybrid sterility is multigenic, with recurrent involvement of Prdm9 and X-linked loci, including Hstx2 . The Dobzhansky–Miller incompatibility between Prdm9 and Hstx2 relates to meiotic recombination and homologous chromosome pairing during the first meiotic prophase. Fertility of Mus musculus musculus × Mus musculus domesticus F1 hybrid females homozygous for the M. musculus musculus Hstx2 locus disproves the dominance theory of Haldane's rule in this particular hybrid sterility model.